Joint Commitment: What It Is and Why It Matters - Margaret Gilbert (Rosenberg & Sellier, 2016)
There is reason to think that a particular concept of joint commitment informs much human behavior. This paper introduces the concept in question and briefly develops one argument for its centrality in human life. This argument focuses on the inherence in many central social phenomena of a particular kind of right.